2014
DOI: 10.1108/msq-07-2013-0121
|View full text |Cite
|
Sign up to set email alerts
|

Mediating effects between World Games identification and licensed merchandise

Abstract: Purpose – The purpose of this paper is to explore consumer decision-making factors related to purchases of licensed merchandise, while focussing on how consumers’ identification with the 2009 World Games (WG), perceptions of quality and attitudes toward collecting, affect the decision-making model with regards to purchasing intention. Design/methodology/approach – The research model is based on the study of Kwak and Kang (2009), but also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…It is generally known that when customer perception of the quality of the service is high, he/she builds positive behavioral intentions and becomes loyal to the company that generates the service [37,38]. The service quality is a salient factor in boosting a company's performance, evoking customers' positive emotional responses and sustaining an enduring valued relationship between the company and its customers [39,40].…”
Section: Airline Service Quality and Its Influencementioning
confidence: 99%
“…It is generally known that when customer perception of the quality of the service is high, he/she builds positive behavioral intentions and becomes loyal to the company that generates the service [37,38]. The service quality is a salient factor in boosting a company's performance, evoking customers' positive emotional responses and sustaining an enduring valued relationship between the company and its customers [39,40].…”
Section: Airline Service Quality and Its Influencementioning
confidence: 99%
“…Previous research has also shown that consumers have an ideal self-image and strive to consume brands that will boost their self-esteem (Carlson et al, 2009). Furthermore, the stronger the link between brand personality and a consumer's self-image, the greater is the likelihood that the consumer will possess a meaningful attitude toward the brand and feel an emotional attachment to it (Bodet and Bernache-Assollant, 2011;Kuenzel and Halliday, 2010;Wu et al, 2012), leading to increased brand loyalty (Cheng et al, 2014;Huang et al, 2014;Malhotra, 1988). Evidence also indicates that brand personality directly influences attitudinal (Buil et al, 2013) and behavioral (Brakus et al, 2009) aspects of loyalty.…”
Section: Effect Of Brand Personality On Customer Loyaltymentioning
confidence: 99%